Celestial navigation - Tyler, Anne. (London, United Kingdom : Vintage, 1996)
By the author of the Pulitzer Prize-winning "Breathing Lessons", this is the tale of Jeremy Pauling, a 38-year-old bachelor who has never left home. The death of his mother leaves him in charge of a ramshackle boarding house and the arrival of a female lodger brings him a challenge he can't handle.
1.Fall, 1960: Amanda -- 2. Spring, 1961: Jeremy -- 3. Spring and summer, 1961: Mary -- 4. Summer and Fall, 1961: Jeremy -- 5. Fall, 1968: Miss Vinton -- 6. Spring, 1971: Jeremy -- 7. Spring and Summer, 1971: Mary -- 8. Spring through Fall, 1971: Olivia -- 9. Fall, 1971: Jeremy -- 10. Spring, 1973: Miss Vinton.
Keywords: AGORAPHOBIA